A global assessment of NASA AIRS v6 and EUMETSAT IASI v6 precipitable water vapor using ground‐based GPS SuomiNet stations. Issue 15 (12th August 2016) - Roman, Jacola; Knuteson, Robert; August, Thomas; Hultberg, Tim; Ackerman, Steve; Revercomb, Hank
Abstract: Satellite remote sensing of precipitable water vapor (PWV) is essential for monitoring moisture in real time for weather applications, as well as tracking the long‐term changes in PWV for climate change trend detection. This study assesses the accuracies of the current satellite observing system, specifically the National Aeronautics and Space Administration (NASA) Atmospheric Infrared Sounder (AIRS) v6 PWV product and the European Organization for the Exploitation of Meteorological Satellite Studies (EUMETSAT) Infrared Atmospheric Sounding Interferometer (IASI) v6 PWV product, using ground‐based SuomiNet Global Positioning System (GPS) network as truth. Elevation‐corrected collocated matchups to each SuomiNet GPS station in North America and around the world were created, and results were broken down by station, ARM region, climate zone, and latitude zone. The greatest difference, exceeding 5%, between IASI and AIRS retrievals occurred in the tropics. Generally, IASI and AIRS fall within a 5% error in the PWV range of 20–40 mm (a mean bias less than 2 mm), with a wet bias for extremely low PWV values (less than 5 mm) and a dry bias for extremely high PWV values (greater than 50 mm). The operational IR satellite products are able to capture the mean PWV but degrade in the extreme dry and wet regimes. Key Points: Ground‐based GPS can provide a reliable and accurate reference for satellite derived PWV observations AIRS and IASI PWV fall within a 5% error in the range of 20‐40 mm relative to ground‐based GPS PWV AIRS and IASI PWV errors exceed 5% for wet (dry bias) and dry (wet bias) extremes of the distribution